OPTIMIZATION OF INTEGRATED DISTRICT ADMINISTRATIVE SERVICES - Ramadha Yanti Parindori; Boby Indra Prayoga; Saima Rambe (Institute of Computer Science (IOCS), 2022)
This study identifies and explains public services, primarily administrative services carried out in Medan Amplas District. The approach method used is qualitative, and data collection is carried out using interviews, observations, documentation, and surveys. The implementation of administrative services in the Medan Amplas sub-district has not been optimal, such as not increasing accessibility, especially for people with disabilities, the low level of employee competence in using Microsoft Office applications so that the service process is slow to the weak level of security at the sub-district office. However, based on the Community Satisfaction Survey (SKM), this study shows that respondents' perceptions of the SKM score of 81.944 are in the class 81.26 to 100.00. With these results, it can be interpreted that the implementation of PATEN in Medan Amplas District has an excellent quality value (A) compared to the results of interviews, field observations, and results of the SKM survey on the implementation of PATEN in Medan Amplas District. Ample can have been implemented well even though it has some drawbacks.